Programmable multi-direction fully integrated chaotic oscillator. (May 2018) - Jin, Jie
Abstract: This paper presents a digitally programmable multi-direction fully integrated chaotic oscillator. Unlike the conventional chaotic oscillators, the proposed digitally programmable multi-direction chaotic oscillator is fully integrated in one single chip, and it achieves lower supply voltage, lower power dissipation and smaller chip area. Moreover, by controlling the digitally programmable MOS switches turning on and off, the presented chaotic oscillator can provide chaotic oscillation in three different directions. The proposed digitally programmable multi-direction fully integrated chaos oscillator is verified with Cadence IC Design Tools. The post-layout simulation results demonstrate that the chaotic oscillator consumes 99.5 mW from ±2.5 V supply voltage, and it takes a compact chip area of 0.177 mm 2 . The integrated chaos oscillator has a wide range of practical application prospects in chaotic communications or other applications demanding portable chaos systems.